KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT LEVERAGE - Rusman Soleman (Jurnal Keuangan dan Perbankan, 2008)
The objective of this research was to identify the effect of firm characteristics (firmsize, and asset growth, and profitability) simultaneously and individually on leverage rate atpublic firm of manufacturer sector listed in Indonesia Stock Exchange (BEI). This research wereexplanatory research, was done by survey method on public firm of manufacturer sector listedin Jakarta Stock Exchange (BEJ). The minimal samples were taken in the amount of 35 firmfrom population amount of 157 which calculated base on Yamane method for cross sectiondata in the year at 2003 2005. Based on multiple regression model of analysis, the resultsshowed that firm characteristics (firm size, and asset growth, and profitability) simultaneouslyand individually have influence on leverage rate at public firm of manufacturer sector listed inIndonesia Stock Exchange (BEI).